الرضا عن التوجيه المدرسي و علاقته بدافعية التعلم لدى تلاميذ السنة الاولى ثانوي دراسة ميدانية بثانوية الامام الغزالي بالأغواط - لبرق رخديجة; كبير نوال; جمال فطام (My University, 2019)
The school guidance plays an important role in determining the student's future career and career and determining its features through making a decision to orient the student towards a particular specialization without the other to satisfy his educational needs and find compatibility between his internal components and potential abilities And readiness and desire of specialization, which was directed towards it to achieve its goals and ambitions, but in light of the large census of students and the high level of competitive aspirations between them to prove the self in light of the changes and effects imposed by the age stage stage adolescence and protect the future project of the student through the guidance services and so the research is important by knowing the impact of satisfaction On the guidance of the school to change the task and motivation of learning in the student and have a direct relationship to the collection and acquisition of different experiences and productivity school, which works to link a positive relationship of the student and his educational environment and highlights the The role of public and effective counseling services plays in school or school guidance in the latter to link the relationship between satisfaction with guidance and motivation to learn